An analysis of terrestrial water storage changes of a karstic, endorheic basin in central Anatolia, Turkey - Koycegiz, Cihangir; Sen, Omer Lutfi; Buyukyildiz, Meral (Elsevier BV, 2023)
Water budget components of endorheic basins of semi-arid and karstic characters are difficult to assess. In this study, we attempt to estimate the water budget components of the Konya Endorheic Basin (KEB), which is a semi-arid, karstic basin in central Anatolia, using The Gravity Recovery and Climate Experiment mission (GRACE) observations and Global Land Data Assimilation System (GLDAS) data over the period 2002-2019. We also investigate the trends and sub-trends in the time series of the hydrometeorological parameters. The results indicate that the available water potential in the basin has a decreasing trend over the study period. Precipitation and evapotranspiration show increasing trends in the basin, however, the other hydrometeorological parameters demonstrate decreasing trends. Both Terrestrial Water Storage Anomaly (TWSA) and groundwater level decrease significantly (20.21 mm/yr and 122.34 mm/yr, respectively). The dry 2008 and subsequent wet year created a hydrological breaking point in the time series. The weights of soil moisture and groundwater storages are relatively large amongst the TWSA components (49.61% and 33.12%, respectively). The surface water storage anomaly comes at the third place with a 14% weight. It is assessed that the groundwater storage system responds to precipitation with a delay of 6 months. Limestone zones respond more sharply to groundwater depletion than alluvial zones. It should be noted that the GRACE and GLDAS data could be used together to successfully estimate the water budget components for sustainable management of the limited water resources of the basin. (c) 2023 European Regional Centre for Ecohydrology of the Polish Academy of Sciences. Published by Elsevier B.V. All rights reserved.